An Efficient LP Rounding Scheme for Replica Placement - Du, Zhihui; Zhang, Sen; Bader, David A.; Hu, Jingkun (IEEE Conference on High Performance Extreme Computing (Online), 2020)
Large fault-tolerant network systems with high Quality of Service (QoS) guarantee are critical in many real world applications and entail diverse replica placement problems. In this paper, the replica placement problem in terms of minimizing the replica placement cost subject to both QoS and fault-tolerant constraints is formulated as a binary integer linear programming problem first and then relaxed as a linear programming problem. Given the optimal fractional linear programming solution, we propose a two-step rounding algorithm to obtain its integer solution. In the first step, a half rounding algorithm is used to simplify the problem. In the second step, a cheapest amortized cost rounding algorithm uses a novel metric, named amortized cost, to make locally optimal rounding decision for the remaining vertices independently. Furthermore, a conflict resolution algorithm is presented to tackle the situations when different vertices make conflicting rounding decisions. Finally, we prove that the proposed two-step rounding algorithm has a 2-approximation ratio when the additional conflict cost meets a given constraint.